Improvement of the control system of network inverters in distributed power supply networks of gas compressor stations - Pavel Yu. Pustokhin; Anatolii M. Ziuzev; Oleg V. Kryukov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2025)
Relevance. The need to maintain the reliability of the power supply system of gas compressor stations in conditions of an increasing proportion of distributed generation using network voltage inverters. Aim. To develop a network inverter control system that does not contribute to reducing the inertia of the power system, maintains operability in case of short-term supply voltage failures and ensures a smooth transition to operation in an autonomous network. Object. Grid inverter as part of a distributed generation source of a gas compressor station, which provides electricity transmission to the network from a DC link. Methods. Theoretical foundations of electrical engineering, electric drive theory, automatic control theory, computer simulation of nonlinear dynamic systems using the Matlab/Simulink software package and numerical solution methods. Results. The authors have developed and described in detail network inverter control system, simulating the behavior of a synchronous machine, as well as taking into account the physical limitations of the converter. Using computer simulation, the approbation of the designed and existing converter control system was carried out. Based on the obtained simulation results, a comparative analysis of the operation of two systems in static and dynamic modes was carried out. Conclusions are drawn about the advantages and disadvantages of the proposed system. Conclusions. The use of virtual synchronous machine type converters in the implementation of distributed generation is one of the ways to preserve the inertia of the power system necessary to maintain stable operation of the electric network of the gas compressor station. The ability to work in an autonomous network of these converters and their smooth transition to this mode will also improve the reliability of the gas compressor station power supply system.